Teoria crítica, neoliberalismo e educação: análise reflexiva da realidade educacional brasileira a partir da reforma educacional de 1990 - Silva, Odair Vieira da [UNESP] (2015)
The text presented here is the result of a research project with thematic focus centered on reflective analysis of Brazilian educational politics, since the educational reform of the 1990s. The overall objective of the research was to analyze the neoliberal reforms imposed by corporations and supranational financial agencies, as the International Monetary Fund (IMF) and the World Bank (WB) and its consequences for education. The initial reflection revolved around the reorganization and capital globalization, since the 1960s. To reflect on the historical materiality of these facts and the demands of late capitalism, we use the theoretical references of Critical Theory. Our theoretical approach has been done by the contributions of Max Horkheimer, Theodor Adorno and Herbert Marcuse, based on two frankfurtians concepts : cultural industry and semiformation. Although today, the ideology of educational reform has proclaimed slogans as universal, quality, equity and efficiency of educational services, what we perceive indeed is the worsening of the educational problems. In this sense, we can conclude that during the last two decades, neoliberal proposals have intensified and crystallized in school spaces. These proposals have built business positions and economistic education, favoring the dominance of instrumental reason, the adaptation and conformity to current economic and social reality.